2011
DOI: 10.1021/ic200646h
|View full text |Cite
|
Sign up to set email alerts
|

“Covalent Hydration” Reactions in Model Monomeric Ru 2,2′-Bipyridine Complexes: Thermodynamic Favorability as a Function of Metal Oxidation and Overall Spin States

Abstract: Density functional theory (DFT) has been used to investigate the plausibility of water addition to the simple mononuclear ruthenium complexes, [(NH(3))(3)(bpy)Ru═O](2+/3+) and [(NH(3))(3)(bpy)RuOH](3+), in which the OH fragment adds to the 2,2'-bipyridine (bpy) ligand. Activation of bpy toward water addition has frequently been postulated within the literature, although there exists little definitive experimental evidence for this type of "covalent hydration". In this study, we examine the energetic dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
(70 reference statements)
1
7
0
Order By: Relevance
“…This prediction gave a solid conceptual foundation to a widely accepted notion that mononuclear metallic systems should, in theory, be tunable toward effective water oxidation. This new mechanistic understanding outlined above led to the development of highly effective multinuclear complexes as well as mononuclear catalysts. …”
Section: Organometallic Catalystssupporting
confidence: 68%
“…This prediction gave a solid conceptual foundation to a widely accepted notion that mononuclear metallic systems should, in theory, be tunable toward effective water oxidation. This new mechanistic understanding outlined above led to the development of highly effective multinuclear complexes as well as mononuclear catalysts. …”
Section: Organometallic Catalystssupporting
confidence: 68%
“…Indeed, evidence for formation of this type of intermediate during catalytic cycling of the "blue dimer" has been obtained in the form of NIR optical spectra in photocatalyzed reactions, 39 pulse radiolysis experiments that characterize "blue dimer"−OH adducts, 36 and theoretical studies that establish the plausibility of this reaction in bipyridine complexes containing highly oxidized Ru centers. 80 However, it is unclear how the unpaired spins on the metal center and ligand would interact in such a species (e.g., {4,5}-bpyOH • ) and, more pointedly, we do not observe any 1 H or 14 N hyperfine contributions that would be indicative of a bipyridyl radical, refer to Figure 7 for the assigned coupling constants. Further, that the {5,5} containing solutions for functionalized bipyridine ligands gives essentially the same EPR spectrum would seem to preclude bipyridine hydroxylation.…”
Section: ■ Discussionmentioning
confidence: 74%
“…An alternative target for the attack would be the ligand radical cation, which has been proposed for the blue dimer. [42,43] Therefore, one water molecule was added to 6 to form 17. We found that the oxo group acts as a general base and removes a proton from the water molecule, concomitant with a nucleophilic attack on one of the benzene carbon atoms by the emerging hydroxide ion.…”
Section: Competing Pathwaysmentioning
confidence: 99%